Europäischer Zinslastenausgleich - eine sinnvolle Alternative zu EZB-Anleihekäufen - Hayo Reimers (Wirtschaftsdienst, 2013)
Im September 2012 hatte die EZB angekündigt, unter bestimmten Bedingungen unbegrenzt Staatsanleihen von Krisenländern aufzukaufen. Diese Maßnahmen führen allerdings zu einem hohen Haftungsrisiko für die übrigen Länder des Euroraums. Welche Vorteile demgegenüber der vom Institut für Weltwirtschaft vorgeschlagene Zinsausgleichsfonds bietet, stellt Hayo Reimers hier dar. – – The eurozone's public debt crisis is not over yet - as displayed in the still substantial yield spreads between 'northern' and 'southern' euro government bonds. Whereas the ECB tried to tackle this problem by announcing (in Sept. 2012) its willingness to conduct unlimited 'outright monetary transactions' to the benefi t of the southern countries, the German 'Institut für Weltwirtschaft (IfW)' offered a less risky option in its 'Kiel policy brief' (Jan. 2013): it suggested narrowing this yield spread by establishing a 'yield spread compensation fund', which would balance out interest payments among euro countries. Though this may sound like the first concrete eurozone bailout mechanism, the idea really is a risk-free debt alleviation tool, matching windfall gains with windfall profi ts without too much of a bailout.
Keywords: E43; G28; H63; 330; Zinsdifferenz; Europäische Wirtschafts- und Währungsunion; Schuldenübernahme; EU-Staaten